Town planning regulation in underground urbanistics. Article 2 - Inna Druzhinina; Anastasia Kholyavko (Проект Байкал, 2022)
The article presents the main problems of underground construction in the aspect of legal regulation and a possible scenario of their solution by amending the urban planning documentation. It also considers the concept of 3D cadastre and its application in different countries.